Is immunoglobulin A nephropathy different in different ethnic populations?. Issue 9 (1st May 2019) - Yeo, See Cheng; Goh, Su Mein; Barratt, Jonathan
ABSTRACT: Immunoglobulin A nephropathy (IgAN) is one of the commonest global patterns of primary glomerulonephritis and remains a leading cause of chronic kidney disease and end‐stage renal disease. The sole diagnostic criterion of IgAN remains the presence of dominant mesangial immunoglobulin A deposits on kidney biopsy. Beyond this defining feature, there is significant heterogeneity in the epidemiology, clinical presentation, renal progression and long‐term outcomes of IgAN in different ethnic populations. Mirroring this heterogeneity in clinical phenotypes, there is also marked ethnic variation in the extent of histopathological lesions observed on kidney biopsy, which may partly explain the well‐documented differences in response to immunomodulatory agents reported in different regions of the world. In parallel, disparities have been identified in genetic association studies and key pathogenic pathways in different ethnic populations. Understanding the basis for these differences in IgAN has important implications for both clinical care and future research. In this review, we will examine the impact of ethnicity on the epidemiology, clinical presentation and outcomes, pathogenesis and genetic associations in IgAN. SUMMARY AT A GLANCE: In this paper, the authors examine key differences in the epidemiology, clinical features and pathogenesis of IgAN in different ethnic populations, and discuss the implications of these differences in clinical care and future research.